Association of serum globulin with all-cause mortality in incident hemodialysis patients. Issue 10 (7th October 2021) - Pai, Alex Y; Sy, John; Kim, Joseph; Kleine, Carola-Ellen; Edward, Jessica; Hsiung, Jui-Ting; Kovesdy, Csaba P; Kalantar-Zadeh, Kamyar; Streja, Elani
ABSTRACT: Background: Serum globulin is a major component of total protein and can be elevated in inflammatory disease states. While inflammation is common in hemodialysis patients and associated with mortality and morbidity, the association between serum globulin and mortality has never been examined in hemodialysis patients. Methods: In a retrospective cohort of 104 164 incident hemodialysis patients treated by a large dialysis organization from 2007 to 2011, we explored the association between baseline serum globulin, albumin: globulin (A:G) ratio and serum protein levels and all-cause, cardiovascular and infection-related mortality with adjustments for demographic variables and laboratory markers of malnutrition and inflammation using Cox proportional hazards models. Results: Patients with a globulin concentration >3.8 g/dL had a higher all-cause and infection-related mortality risk hazard ratio [HR] 1.11 [95% confidence interval (CI) 1.06–1.16] and HR 1.28 [95% CI 1.09–1.51], respectively in the fully adjusted model when compared with the reference group of 3.0– <3.2 g/dL. In addition, patients with an A:G ratio <0.75 had a 45% higher all-cause mortality hazard [HR 1.45 (95% CI 1.38–1.52)] and patients with total serum protein <5.5 g/dL had a 34% higher risk of death [1.34 (95% CI 1.27–1.42)] when compared with the reference (A:G ratio 1.05– <1.15 and total serum protein 6.5– <7 g/dL). Conclusions: Among incident hemodialysis patients, a higher globulin level was associated with a higher mortality risk independent of other markers of malnutrition and inflammation, including albumin. A lower A:G ratio and serum protein was also associated with a higher mortality hazard. The mechanisms that contribute to elevated serum globulin should be further explored.